Jim Harris "mythical beasts and Human Rights": a linguistic approach to Human Rights - Garrido Martín, Joaquín (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2017)
This paper studies the analysis of human rights offered by Jim Harris, former Professor of Philosophy of Law in Oxford, in a lecture given to the Scientific Society of Authors shortly before his death. According to Harris, a sound understanding of human rights must conceive them in the linguistic context in which they are employed (linguistic approach). Only in this context they acquire the meaning they have. In the reading of Professor Harris we are assisted by one of his disciples, Timothy Endicott, with a work he published in response to Harris. The main thesis argues that with the linguistic method we could never give an account of the existence of human rights, since that would make universal truths depend on linguistic conventions. This leads Prof. Endicott to develop a new list of rights regardless of their applications in the language (material approach). doi: https://doi.org/10.20318/universitas.2017.3543